SARS-CoV2 Nsp1 is a metal-dependent DNA and RNA endonuclease - Salgueiro, Bruno A. (2024)
Funding Information: Open access funding provided by FCT|FCCN (b-on). This study was financially supported by the Portuguese Fundação para a Ciência e Tecnologia (FCT), Project MOSTMICRO-ITQB with references UIDB/04612/2020 and UIDP/04612/2020, iNOVA4Health (UIDB/04462/2020 and UIDP/04462/2020), and LS4FUTURE Associated Laboratory (LA/P/0087/2020). BAS is recipient of FCT PhD4COVID grant SFRH/BD/08066/2020; RGM is a recipient of an FCT CEEC contract (CEECIND/02065/2017); MS and EM are recipients of FCT DL57; CVR is recipient of FCT Institutional CEEC. Publisher Copyright: © The Author(s) 2024.